Study on Antiinflammatory Effect of Ethanolic Extract of Ginger Leaves (Zingiber officinale) in Albino Rats (Rattus norvegicus) - Gisti Respati Riyanti; Endang Ediningsih; Amelya Augusthina Ayusari (Nexus Biomedika, 2015)
Background: Inflammation is a local protective response which is potentially hazard. Ginger (Zingiber officinale) contains flavonoid which has anti-inflammatory effect. Existing research has used ginger rhizomes as its material, whereas flavonoid in ginger leaves is bigger than the rhizome. This research aimed to investigate the anti-inflammatory effect of ethanolic extract of ginger leaves in albino rats (Rattus norvegicus). Methods: This research was a laboratory experimental with posttest only controlled group design. This research was conducted at Setia Budi University. The subjects were 25 albino male rats 3 months old, weight 150 gr, which were taken by purposive sampling. The subjects were divided equally into 5 groups randomly, which negative control group (KN) were given normal saline and positive control (KP) were given indomethacin whereas test group 1 (KU1), test group 2 (KU2) and test group 3 (KU3), in order, were given 20 mg, 40 mg and 80 mg of ethanolic extract of ginger leaves per 100 gr of body weight orally. Inflammation induction was done by injection of 0.05 mlcarrageenan 1% of sub plantar. Rats foot edema volume was observed every hour for 6 hours after injection. Statistical analysis of the data was done including one way-Anova, Kruskal-Wallis and Mann Whitney test. Results: The greatest inhibition of edema volume was at the 6th hour, KP (74.07%), KU3 (74.07%), KU2 (66.67%) and KU1 (48.15%). The Kruskal-Wallis test showed significant differences among 5 groups with p=0.002 (p<0.05). The Mann-Whitney test showed p=0.068 for KP- KU1, p=0.429 for KP- KU2 and p=0.910 for KP-KU3. Conclusions: The ethanolic extract of ginger leaves has anti-inflammatory effect in albino rats equivalent to indomethacin on the sixth hour after carrageenan induction. Keywords: ginger leaves, Zingiber officinale, anti-inflammatory, carrageenan, albino rats